Strategi Kepala Madrasah dalam Membangun Jiwa Enterpreneurship Peserta Didik - asichul in'am; mohamad mustafid hamdi (Intizam, Jurnal Manajemen Pendidikan Islam, 2022)
Entrepreneurs have an important role in madrasas, every student should have entrepreneurial skills so that in society or in the future they can develop them. The head of the madrasa has a very heavy task in managing these entrepreneurs, while the strategy that can be used in entrepreneurial education is by learning. With learning students can recognize the basic theories in entrepreneurial education. Next is the entrepreneurial practicum, where students practice directly in the field so that they can experience real entrepreneurial education. In carrying out entrepreneurial education, there are several programs that can support developing entrepreneurial education, namely bazaar programs, buying and selling in schools and also training in entrepreneurial education skills.